Examination of energy damping behavior of fiberglass reinforced sandwich structures with extruded polystyrene core material - Yavuz, Ibrahim; Senol, Baris; Simsir, Ercan (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
Composite materials are defined as new materials formed by combining two or more materials that do not mix, leveraging the best properties of each constituent. Composite materials are used in important industrial sectors such as aerospace and automotive due to their superior properties. In this study, XPS (extruded polystyrene) polymer foam was utilized as the core material. Glass fibers were combined with resin in a total of eight and twelve layers and applied to both the top and bottom of the core structure. Production involved both manual laying and vacuum bagging methods. Two types of glass fiber, weighing 200 g/m2 and 300 g/m2 , were employed. After production, the composites were cut to standardized dimensions, followed by three-point bending and low-speed impact tests. Impact experiments were conducted with a constant energy of 50 J. Results showed that the 200 g/m2 glass fiber composites experienced perforation in the eight-layer samples and rebound in the twelve-layer samples. Although greater deformation was observed in the impact tests of the 300 g/m2 glass fiber composites in the eight-layer samples compared to the twelve-layer samples, a rebound occurred in both. In three-point bending tests, the bending strength increased as the number of layers increased, and at the same number of layers, composites with 300 g/m2 properties showed higher strength than 200 g/m2 composites.